Corporate Governance and the Communication Patterns of Malaysian Listed Corporations - Ho, Poh-Ling; Tower, Greg; Taylor, Grantley (Curtin University of Technology, 2009)
The study examines determinants of voluntary disclosure of categories of information in the annual reports of 100 Malaysian listed firms over three very fundamental time periods (1996, 2001 and 2006). These periods represent the pre-financial crisis period, the middle period adjustments to the 1997 Asian financial crisis, and the latter post-Enron driven changes. Major changes to financial reporting and corporate governance rules since the 1997 crisis provided the stimulus for extensive regulatory change. Using a self-constructed voluntary disclosure index, the findings reveal there is a marked increase in the extent of voluntary disclosure of all the five main categories of disclosure over the eleven-year period. The results reveal that firms with enhanced corporate governance structure make more extensive disclosure in all categories of information in 2001 and, in particular, 2006. These results provide evidence that improving the corporate governance structure in Malaysian regulatory process clearly improves corporate disclosure and transparency.